Platelet-leukocyte-rich plasma (L-PRP) prevents the collagen III degradation and impairs the bone matrix development in artificial defect of rabbit calvaria, associated with suppression of the immunohistochemical expression of MMP-2 and MMP-9 - Anselmo Gabriel Wruck Garcia; Rafaela Scariot; Melissa Rodrigues de Araujo; Emanuelle Juliana Cunha; Jaqueline Muller Henn; João Ricardo de Almeida Grossi; Tatiana Miranda Deliberador; João Cesar Zielak; Allan Fernando Giovanini (Revista Sul-Brasileira de Odontologia, 2015)
Because L-PRP constitutes an important source of growth factor that is associated with osteogenesis and fibrogenesis, the aim of this study was to evaluate the effect of L-PRP on the presence of collagen III and MMP-2 and MMP-9, while comparing these results by means of a histomorphometric analysis of bone matrix and fibrous deposition on bone repair. Material and methods: Four bone defects of 8 × 2 mm were created on the calvaria of 21 rabbits. The surgical defects were treated with either particulate autograft, particulate autograft mixed with L-PRP, or L-PRP alone. Animals were euthanized at 2, 4, and 6 weeks postoperative. Histomorphometric and immunohistochemical analyses were performed to assess repair time, as well as the expression of collagen III and MMPs. Results: In contrast to the results of the L-PRP-free groups, the histomorphometric results of the L-PRP groups demonstrated intense fibrotic deposition along with hindered bone matrix deposition. These results coincided with the larger occurrence of diffuse collagen III deposition and the scarce presence of MMP2 and -9 spread among the fibrous tissue. Conclusion: Thus, the results suggest that L-PRP not only induces an intense fibrosis rich in collagen III, which is not degraded, but also suppresses MMP-2 and -9 expressions, mimicking a similar pathological event as that of a cleft-palate or cranial suture.